FREINET, VIGOSTKY AND BAKHTIN: A POSSIBLE APPROACH TO ACCESS WRITING CULTURE - Guizellim Simoes Girotto, Cyntia Graziella [UNESP]; Ferreira Da Sllva, Greice; Magalhaes, Cassiana (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
This study aims to reflect on pedagogical practices about the culture of reading and writing from the perspective of the Cultural-Historical Theory (CHT) and Bakhtin's theory of enunciation, seeking a possible dialogue with the ideals of Freinet's thinking and techniques. It is a research carried out in a public municipal institution of Sao Paulo State countryside with five and six-year-old children. The criterion for class selection was the fact that the children had experiences in school in the context of Freinet's techniques. After data collection and careful analysis, it is possible to affirm that there is a possibility of dialogue between Freinet, Vigotsky and Bakhtin, and, mainly, teacher's theoretical appropriation of this existing approximation potentiates the pedagogical practices about reading and writing.
Keywords: Pedagogical Practices; Historical-Cultural Theory; Freinetian thinking; Written culture; Reading